2009
DOI: 10.1111/j.1365-3164.2008.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

TheABCB1‐1Δmutation is not responsible for subchronic neurotoxicity seen in dogs of non‐collie breeds following macrocyclic lactone treatment for generalized demodicosis

Abstract: P-glycoprotein (P-gp), encoded by the multiple drug resistance gene ABCB1 (also known as MDR1), is an integral component of the blood brain barrier crucial in limiting drug uptake into the central nervous system. Altered expression or function of P-gp, as seen in dogs of the collie lineage homozygous for the nt228(del4) mutation of the ABCB1 gene (ABCB1-1Delta), can result in potentially fatal neurotoxicosis, especially following administration of systemic macrocyclic lactones (SML). Occasionally, dogs from un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…11,12,24,25 Although the 4-bp deletion mutation in the canine MDR1 gene was often responsible for the hypersensitivity for the substrate drugs of P-gp especially in Collies, 20,22 it was reported that non-Collie dogs lacking this mutation were affected with subchronic neurotoxicity following administration ivermectin, milbemycin, and/or moxidectin for generalized demodicosis. 2 Recently, a novel insertion mutation of the canine MDR1 gene was identified in an ivermectinsensitive Border Collie, although the correlation between the insertion mutation and the ivermectin-sensitive phenotype in this dog was not clarified completely. 13 In human beings, at least 3 single nucleotide polymorphisms were found in the human MDR1 gene, 17 which may be related to abnormal sensitivity to multiple drugs.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,24,25 Although the 4-bp deletion mutation in the canine MDR1 gene was often responsible for the hypersensitivity for the substrate drugs of P-gp especially in Collies, 20,22 it was reported that non-Collie dogs lacking this mutation were affected with subchronic neurotoxicity following administration ivermectin, milbemycin, and/or moxidectin for generalized demodicosis. 2 Recently, a novel insertion mutation of the canine MDR1 gene was identified in an ivermectinsensitive Border Collie, although the correlation between the insertion mutation and the ivermectin-sensitive phenotype in this dog was not clarified completely. 13 In human beings, at least 3 single nucleotide polymorphisms were found in the human MDR1 gene, 17 which may be related to abnormal sensitivity to multiple drugs.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no specific safe and effective antidote available to treat this neurotoxicity and symptomatic and supportive treatment is indicated (Geyer & Janco 2012). Toxicity related to the mdr-1 gene mutation should not be confused with the subchronic neurotoxicity that could follow macrocyclic lactone administration in all dogs (Bissonnette et al 2008).…”
mentioning
confidence: 99%
“…Adverse neurological effects have also been reported in dogs of many different breeds with a normal MDR1 gene (Bissonnette and others 2009). In these dogs the signs usually occur late in the course of the therapy, are less severe and respond to a reduction of the ivermectin dose.…”
Section: Treatmentmentioning
confidence: 99%